Five new species of Parapercis (Perciformes: Pinguipedidae) from southeast Asia and northwest Australia - Johnson, Jeffrey W.; Motomura, Hiroyuki (Zootaxa, 2017)
Five new species of sandperch (Pinguipedidae: Parapercis) from southeast Asia and northwest Australia are described. Parapercis soliorta sp. nov., known from a single specimen acquired from the Iloilo Central Market, taken off Iloilo, Panay Island, Philippines, is readily distinguished by a unique colour pattern including a series of nine brilliant yellow-ringed red spots along the body and caudal fin. Parapercis rubricaudalis sp. nov. is described from 15 specimens trawled between Dampier and Cape Leveque, Western Australia in 70–119 m and a single specimen taken by aquarium fish collectors off Zambales, Luzon, Philippines. It has the posterior end of the opercular ridge armed with two or three strong spines, the margin of the preopercle, subopercle and interopercle strongly serrated, and colouration including six broad irregular orange to reddish bands across the body, and the pelvic fins and lower third of the caudal fin crimson-red. A complex of three closely related species, Parapercis flavipinna sp. nov. from the Philippines, Parapercis caudopellucida sp. nov. from Myanmar and Parapercis hoi sp. nov. from northwest Australia and the Philippines, share a series of six or seven irregular dusky double blotches along the sides, a series of small black spots along the base of the soft dorsal-fin, a pair of dusky blotches on the caudal-fin base, and mostly similar meristic values. Parapercis hoi sp. nov. is known from four specimens trawled off Broome, Western Australia, in 97–109 m and one specimen trawled in the Sibuyan Sea, Philippines, in 73–84 m. It may be distinguished from its two closest congeners by cycloid cheek scales, a distinctive anal-fin colouration, and lower pectoral-fin ray, gill raker and lateral-line scale counts. Parapercis caudopellucida sp. nov., trawled in 125–129 m in the Andaman Sea off southern Myanmar, is described from two specimens. It differs from its two closest congeners most obviously by cycloid cheek scales, caudal-fin colouration, and the presence of a dusky bar extending posteroventrally from the tip of the maxilla to the anteroventral edge of the preopercle. Parapercis flavipinna sp. nov. is described from two specimens acquired from the Iloilo Central Market, taken off Iloilo, Panay Island, in the Philippines. It is distinguished most readily by the presence of ctenoid cheek scales and colouration including rows of bright yellow spots on the anal and caudal fins, a yellow upper lip, a series of yellow streaks and spots on the head, and fleshy pectoral-fin base with a large dark purplish grey blotch followed by a distinct white-edged black bar.